Step width and frontal plane trunk motion in bipedal chimpanzee and human walking. Issue 125 (December 2018) - Thompson, Nathan E.; O'Neill, Matthew C.; Holowka, Nicholas B.; Demes, Brigitte
Abstract: Human bipedalism is characterized by mediolateral oscillations of the center of mass (CoM) between the feet. The preferred step widths and CoM oscillations used by humans likely represent a trade-off of several factors (e.g., stance and swing phase costs). However, it is difficult to assess whether human frontal plane control strategies are unique given few detailed data on frontal plane motion during facultative bipedalism in apes. Here, we collected three-dimensional kinematic and kinetic data in humans and chimpanzees to investigate the relationship between step width, mediolateral CoM motion, frontal plane trunk kinematics, and CoM power during bipedalism. Chimpanzee bipedalism entails mediolateral CoM oscillations and step widths that are (scaled to lower/hind limb length) three times larger than those of humans. Chimpanzees use a combination of linear and angular motion of the trunk and list the entire trunk, and especially thorax, over the stance side foot, generating large mediolateral shifts in the CoM, whereas humans utilize little angular motion within the trunk. Larger mediolateral CoM motions do not have a significant effect on CoM power. Similarities between bipedal chimpanzees and other bipedal non-human primates (macaques and gibbons) indicate that narrow CoM motions are unique to humans and are likely due to our adducted hips and valgus knees. Valgus knees appear early in the human fossil record (∼3.6 Ma), contemporaneous with the Laetoli footprints. However, fossils attributed to Ardipithecus ramidus (∼4.4 Ma) suggest that the earliest hominins may have lacked a hominin-like degree of knee valgus. If correct, this suggests that this species may have used wide steps, larger mediolateral CoM motions, and perhaps larger trunk motions during bipedal walking. Finally, we present a novel means to estimate mediolateral CoM motion from trackway step width, and estimate that the Laetoli G track maker used CoM motions within the human range.